Analysis of voltage scaling effects in the design of resilient circuits - Gibiluka, Matheus (2016)
Although the advancement of semiconductor technology enable the fabrication of devices with increasingly reduced propagation delay, potentially leading to higher operating frequencies, manufacturing process variability grows very aggressively in modern processes. To cope with growing variability phenomena, significant delay margins need to be added to clock signal’s periods, to ensure timing closure, which limits performance gains and constrains power efficiency. Among the several techniques that have been explored in the last decades to address these problems, three are quite relevant and promising either in isolation or combined: voltage scaling, asynchronous circuits and resilient architectures. This work investigates how voltage scaling affects circuit path delays, and produces three sets of original contributions. The first set establishes a technique to ensure that circuits synthesized with a reduced library achieve results comparable to the full library, while keeping functionality at low supply voltages. The second set of contributions composes a method to extend the voltage corners supported by standard cell libraries. This takes place through new library characterization techniques. The third set of contributions provides insights on the effects of voltage scaling in the design of resilient circuits. This analysis evaluates supply voltages in super- and sub-threshold levels.